A sodium ion battery and a formation method thereof
By adding sodium ions to the negative electrode material of sodium ion batteries and using sodium-rich titanium phosphate potassium carbon composite material, combining a specific chemical charging and discharging system and K lithium ion additives in the electrolyte, the problem of sodium ion consumption in the electrolyte caused by the exchange of potassium ions and sodium ions is solved, and high-efficiency first charge and discharge and long-term cycle stability are achieved.
Patent Information
- Application Number
- CN202510131780.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-02-06
AI Technical Summary
When potassium titanium phosphate is used as the negative electrode material in a sodium ion battery, the exchange between potassium ions and sodium ions leads to the consumption of sodium ions in the electrolyte, affecting the normal operation of the battery and the first charge and discharge efficiency.
Sodium-rich titanium phosphate potassium carbon composite material is used as the negative electrode material, and sodium ions are added to the negative electrode active material to reduce the exchange of potassium ions and sodium ions. At the same time, a specific chemical charging and discharging system is set up, and a trace amount of K lithium ion additive is added to the electrolyte to form a protective film and inhibit the exchange of K-Na ions.
It effectively suppresses the exchange of K-Na ions, maintains the concentration of sodium ions in the electrolyte, improves the first charge and discharge efficiency of the battery by more than 90%, and ensures the long-term cycle stability of the battery.
Smart Images

Figure CN119560662B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery and a formation method thereof. Background Art
[0002] As a key component in energy storage systems, the electrochemical performance of secondary ion batteries is particularly important. Among them, secondary sodium ion batteries have advantages such as low cost and excellent low-temperature performance, and the electrode material directly determines the electrochemical performance of the battery.
[0003] In the prior art, the negative electrode material of sodium ion batteries is usually sodium titanium phosphate. The high potential of sodium titanium phosphate comes from the fact that in this crystal structure, only Ti-OP bonds exist. 3- Polyanion to Ti 4+ It has a strong inductive effect, making Ti 4+ To Ti 3+ The electrochemical redox potential corresponding to the valence change is 2.1v (vs Na / Na + For the titanium phosphate compound ATiOPO4, since the covalency of the titanium-oxygen-titanium bond is weaker than the oxygen-phosphorus bond, the redox potential can be significantly reduced to 1.2-1.5V (vs Na / Na + ).
[0004] Among various titanium-based phosphate negative electrode materials, potassium titanyl phosphate (KTiOPO4) has a larger cross cavity, and KTiOPO4 has the lowest potential of 1.23V, which has great potential in achieving faster ion dynamics and lower cycle strain in sodium-ion batteries. However, when KTiOPO4 is used as a negative electrode material for sodium-ion batteries, potassium ions will be replaced by sodium ions through ion exchange during the charge and discharge cycle. This exchange reduces the initial charge and discharge efficiency of the battery and consumes sodium ions in the electrolyte, affecting the normal operation of the battery. How to design active materials and batteries to ensure the normal operation of the battery is an urgent problem to be solved. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a sodium ion battery and a formation method thereof. A sodium-titanium-rich potassium titanyl phosphate carbon composite material is used as a negative electrode. Sodium ions are added to the negative electrode active material to reduce the consumption of Na ions in the electrolyte due to K-Na ion exchange in the early charge and discharge process of the potassium titanyl phosphate, thereby maintaining the sodium ion concentration in the electrolyte unchanged. A specific formation charge and discharge system is set to further inhibit the exchange of K ions with Na ions in the electrolyte, thereby ensuring that the initial charge and discharge coulomb efficiency is higher than 90%, and the battery after activation can be discharged according to a normal charge and discharge voltage.
[0006] In order to solve the above technical problems, the present invention provides a sodium ion battery formation method, comprising the following steps:
[0007] S1. The sodium ion battery to be formed is allowed to stand for 15-60 minutes at a temperature of 60-92°C and a pressure of 0.2-0.3MPa;
[0008] The negative electrode of the sodium ion battery to be formed comprises a sodium-rich potassium titanyl phosphate carbon composite material, wherein the molecular formula of the sodium-rich potassium titanyl phosphate is K 1-x Na x+y TiO (PO4) 1-y M y , wherein x=0-0.8, y=0-0.8, x+y=0.5-0.8, M is a tetravalent anion group; the electrolyte of the sodium ion battery to be formed includes a potassium ion additive;
[0009] S2, at a temperature of 40-60°C and a pressure of 0.3-0.5MPa, charge at a rate of 0.02-0.2C to the activation voltage upper limit Vact max , and then discharge to the activation voltage lower limit Vact min ;
[0010] Among them, Vact max =V max -V δ , Vact min =V min + V δ , V δ =0.4-0.6v, V max and V min They are respectively the upper and lower voltage limits for normal battery operation.
[0011] The present invention aims at the consumption of Na ions in the electrolyte due to K-Na ion exchange in the potassium titanyl phosphate negative electrode material during the early charge and discharge process. Na ions are added to the negative electrode active material to reduce this replacement, keep the concentration of the electrolyte unchanged, and facilitate the long-term cycle stability of the battery.
[0012] The present invention is combined with a specific formation system. During the charging process of the negative electrode material, Na ions are first deintercalated and then replaced by K-Na ions. The battery is activated within a certain voltage range, and the activation voltage range is just within the deintercalation voltage V 脱嵌 and the switching voltage V 交换The potential energy of K-Na ion exchange is not reached. At the same time, a trace amount of K lithium ion additive is added to the electrolyte, which is enriched on the surface of the negative electrode during the activation process to form a protective film, which inhibits the exchange of K-Na ions and ensures that the first charge and discharge coulomb efficiency is higher than 90%; after the activation, a protective film is formed on the surface of the negative electrode to block the contact between the negative electrode and the electrolyte. The battery is charged and discharged according to the normal charge and discharge voltage. When the voltage reaches the K-Na ion exchange potential, the presence of the protective film avoids the consumption of Na ions in the electrolyte; in addition, in S1, the temperature is high and the pressure is low, for better infiltration, while in S2, the temperature is low and the pressure is high, which is suitable for battery activation.
[0013] Further, the M is SiO4 4- or P2O7 4- , ensuring that there are enough cation sites to provide Na ion sites.
[0014] Furthermore, the K 1-x Na x+y TiO (PO4) 1-y M y In the example, the values of x and y may be: x=0.5, y=0; x=0.1, y=0.4; x=0.8, y=0; x=0, y=0.8; x=0.4, y=0.2; x=0.3, y=0.4, etc., including but not limited to these.
[0015] Furthermore, the potassium ion additive is selected from potassium bis(fluorosulfonyl)imide (KFSI) and / or potassium bis(trifluorosulfonyl)imide (KTFSI).
[0016] Furthermore, the amount of the potassium ion additive added is 0.1%-1% of the mass of the electrolyte.
[0017] Furthermore, the mass ratio of sodium-rich potassium titanyl phosphate to carbon in the sodium-rich potassium titanyl phosphate carbon composite material is (0.7-0.99): (0.01-0.3).
[0018] Furthermore, the preparation method of the sodium-rich potassium titanyl phosphate carbon composite material is: K source material, Na source material, Ti source material, P source material, M source and carbon source material are evenly mixed and dried to obtain a precursor powder, the precursor powder is sintered in an inert atmosphere, and crushed after cooling.
[0019] Furthermore, the sodium ion battery to be formed also includes a positive electrode, and the positive electrode includes sodium iron pyrophosphate, the molecular formula of which is Na 4-a Fe 3-b (PO4)2 (P2O7), where a=0-1, b=0-1.
[0020] Furthermore, the electrolyte solution also includes an electrolyte salt, and the electrolyte salt is selected from one or more of sodium hexafluorophosphate, sodium perchlorate, sodium bis(oxalate)borate, sodium bis(salicylate)borate and sodium tetraphenylborate.
[0021] Furthermore, the electrolyte also includes an organic solvent, and the organic solvent is selected from one or more of ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate and diethylene glycol dimethanol ether.
[0022] The second aspect of the present invention provides a sodium ion battery prepared by the formation method described in the first aspect.
[0023] Beneficial effects of the present invention:
[0024] The present invention adopts a sodium-rich potassium titanyl phosphate carbon composite negative electrode to inhibit K-Na exchange, avoid consumption of Na ions in the electrolyte, keep the concentration of the electrolyte unchanged, and improve the long-term cycle stability of the battery.
[0025] The present invention cooperates with setting a specific formation system, activates within a voltage range that does not reach the K-Na ion exchange potential, and the K lithium ion additive in the electrolyte is enriched on the negative electrode surface to form a protective film during the activation process, thereby inhibiting the exchange of K-Na ions, ensuring that the first charge and discharge coulomb efficiency is higher than 90%, and the cycle stability is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 is K of the present invention 0.2 Na 0.8 dQ / dV curve of battery with TiOPO4 carbon composite material as negative electrode active material. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The present invention relates to a sodium ion battery formation method, comprising the following steps:
[0030] S1. The sodium ion battery to be formed is allowed to stand for 15-60 minutes at a temperature of 60-92° C. and a pressure of 0.2-0.3 MPa; wherein the negative electrode of the sodium ion battery to be formed comprises a sodium-rich potassium titanyl phosphate carbon composite material, and the molecular formula of the sodium-rich potassium titanyl phosphate is K 1-x Na x+y TiO (PO4) 1-y M y , wherein x=0-0.8, y=0-0.8, x+y=0.5-0.8, M is a tetravalent anion group; the electrolyte of the sodium ion battery to be formed includes a potassium ion additive;
[0031] S2, at a temperature of 40-60°C and a pressure of 0.3-0.5MPa, charge at a rate of 0.02-0.2C to the activation voltage upper limit Vact max , and then discharge to the activation voltage lower limit Vact min Among them, Vact max =V max -V δ , Vact min =V min + V δ , V δ =0.4-0.6v, V max and V min They are respectively the upper and lower voltage limits for normal battery operation.
[0032] In this embodiment, in view of the consumption of Na ions in the electrolyte by K-Na ion exchange in the potassium titanyl phosphate negative electrode material during the early charge and discharge process, Na ions are added to the negative electrode active material to reduce this replacement, avoid the consumption of Na ions in the electrolyte, keep the concentration of the electrolyte unchanged, and be beneficial to the long-term cycle stability of the battery; in conjunction with setting a specific formation system, since during the charging process of the negative electrode material, Na ions are first deintercalated and then replaced by K-Na ions, the battery is activated within a certain voltage range, and the activation voltage range is just within the deintercalation voltage V 脱嵌 and the switching voltage V 交换 At the same time, a small amount of K lithium ion additive is added to the electrolyte, which is enriched on the surface of the negative electrode to form a protective film during the activation process, inhibiting the exchange of K-Na ions and ensuring that the first charge and discharge coulomb efficiency is higher than 90%; after the activation, a protective film is formed on the surface of the negative electrode to block the contact between the negative electrode and the electrolyte, and the battery is charged and discharged at a normal charge and discharge voltage. When the voltage reaches the K-Na ion exchange potential, K-Na ions are realized inside the negative electrode active material to avoid the consumption of Na ions in the electrolyte.
[0033] As an embodiment, the M is SiO4 4- or P2O7 4- , ensuring that there are enough cation sites to provide Na ion sites; the K 1-x Na x+y TiO (PO4) 1-y M y In the example, the values of x and y may be: x=0.5, y=0; x=0.1, y=0.4; x=0.8, y=0; x=0, y=0.8; x=0.4, y=0.2; x=0.3, y=0.4, etc., including but not limited to these.
[0034] As an embodiment, the potassium ion additive is selected from potassium bis(fluorosulfonyl)imide (KFSI) and / or potassium bis(trifluorosulfonyl)imide (KTFSI); the added amount of the potassium ion additive is 0.1%-1% of the mass of the electrolyte.
[0035] As an embodiment, the mass ratio of sodium-rich potassium titanyl phosphate and carbon in the sodium-rich potassium titanyl phosphate carbon composite material is (0.7-0.99): (0.01-0.3); the preparation method of the sodium-rich potassium titanyl phosphate carbon composite material is: K source material, Na source material, Ti source material, P source material, M source and carbon source material are uniformly mixed according to the atomic ratio of the sodium-rich potassium titanyl phosphate carbon composite material and dried to obtain a precursor powder, the precursor powder is sintered at 700-850°C in an inert atmosphere (argon or nitrogen) for 4-24h, and crushed after cooling. As a specific example, the K source material is at least one of KOH, K2CO3, KH2PO4 and potassium acetate, the Na source material is at least one of NaOH, Na2CO3, NaH2PO4 and sodium acetate, the Ti source material is at least one of titanyl sulfate, TiO2, tetrabutyl titanate and titanium tetrachloride, the P source material is at least one of H3PO4, NH4H2PO4, (NH4)2HPO4, P2O5, the M source material is at least one of SiO2 and a phosphorus source, and the carbon source material is at least one of acetylene black, graphite, Super P, sucrose and glucose.
[0036] As an embodiment, the sodium ion battery to be formed further comprises a positive electrode, wherein the positive electrode comprises sodium iron phosphate pyrophosphate, the molecular formula of which is Na 4-a Fe 3-b (PO4)2 (P2O7), where a=0-1, b=0-1.
[0037] As an embodiment, the electrolyte further includes an electrolyte salt, which is selected from one or more of sodium hexafluorophosphate, sodium perchlorate, sodium bis(oxalate)borate, sodium bis(salicylate)borate and sodium tetraphenylborate; the electrolyte further includes an organic solvent, which is selected from one or more of ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate and diethylene glycol dimethanol ether. Example 1
[0038] This embodiment relates to the preparation of a titanium-based phosphate carbon composite material, comprising the following steps: 1-x Na x+y TiO (PO4) 1-y M y Atomic ratio and K 1-x Na x+y TiO (PO4) 1-y M y The K source material K2CO3, the Na source material Na2CO3, the Ti source material titanyl sulfate, the P source material H3PO4, the M source SiO2 or H3PO4 and the carbon source material acetylene black are mixed uniformly and dried to obtain a precursor powder, the precursor powder is sintered at 800°C for 12h in an inert atmosphere, and then pulverized after cooling to obtain a potassium titanyl phosphate carbon composite material, and K is prepared by adjusting the x and y values. 0.5 Na 0.5 TiOPO4 carbon composites, K 0.9 Na 0.5 TiO (PO4) 0.6 (P2O7) 0.4 Carbon composite materials, K 0.2 Na 0.8 TiOPO4 carbon composites, KNa 0.8 TiO(PO4) 0.2 (P2O7) 0.8 Carbon composite materials, K 0.6 Na 0.6 TiO(PO4) 0.8 (P2O7) 0.2 Carbon composite materials, K 0.6 Na 0.6 TiO(PO4) 0.8 (SiO4) 0.2 Carbon composite materials, K 0.7 Na 0.7 TiO(PO4) 0.6 (SiO4) 0.4 carbon composites and conventional KTiOPO4 carbon composites. Example 2
[0039] This embodiment relates to a method for preparing a sodium ion battery to be formed, comprising the following steps:
[0040] (1) The titanium-based phosphate carbon composite material prepared in Example 1 was used as the negative electrode active material, and sodium iron pyrophosphate Na 3.5 Fe 2.9 (PO4)2(P2O7) is a positive electrode active material, and the positive and negative electrode active materials, conductive carbon black, polyvinylidene fluoride, and N-methyl-2-pyrrolidone are uniformly mixed in a mass ratio of 97:2:1:150 to obtain positive and negative electrode slurries respectively;
[0041] (2) The positive and negative electrode slurries were coated on an aluminum substrate respectively, dried at 120°C, rolled at 4.0 MPa, and die-cut into positive electrode sheets with a size of 56 mm*43 mm and negative electrode sheets with a size of 58 mm*45 mm;
[0042] (3) According to the order of "positive electrode sheet, separator, negative electrode sheet, separator", the stacking layers are 9 positive electrode sheets and 10 negative electrode sheets. After making the welding tabs, the top and bottom edges are encapsulated with pre-punched aluminum plastic film. The dry battery cell is placed in a vacuum oven with a vacuum degree of -0.095MPa and a temperature of 120℃ for 12 hours to obtain a dry battery cell; the dry battery cell is taken out and placed in a glove box, and the side encapsulation is completed after injecting an electrolyte with a concentration of 1mol / L to obtain a sodium ion battery to be formed. Among them, the separator is a 9μm PE film, the solvent of the electrolyte is ethylene carbonate, the electrolyte salt is sodium hexafluorophosphate, and the addition of potassium ion additives is shown in Table 2.
[0043] Test Example 1
[0044] Normal charge and discharge cut-off voltage V of batteries with different negative electrode active materials max 、V min Determination.
[0045] The battery prepared in Example 2 was subjected to a charge and discharge test, and the normal charge and discharge voltage of the battery was determined according to the dQ / dV curve. The charge and discharge cut-off voltage (the upper or lower voltage limit of normal operation) was determined when dQ / dV was equal to 0. 0.2 Na 0.8 The dQ / dV curve of the battery with TiOPO4 carbon composite as negative electrode active material is as follows Figure 1 As shown, it can be seen that its normal charge and discharge voltage is 0.5-3v. The normal charge and discharge voltage of each negative electrode active material battery is shown in Table 1.
[0046] Table 1
[0047]
[0048] It can be seen from Table 1 that the electronegativity of the P2O7 anion group is relatively high. As the P2O7 content increases, the battery voltage shifts toward a higher voltage. The electronegativity of the SiO4 anion group is lower than that of PO4. Therefore, although the number of cations can be increased, the overall battery voltage decreases.
[0049] Test Example 2
[0050] The first coulombic efficiency (first efficiency) and cycle stability under different formation conditions were determined.
[0051] First coulombic efficiency test: The sodium ion battery prepared in Example 2 was placed at 80°C and 0.25 MPa for 40 min, and then charged at 45°C and 0.4 MPa at a current rate of 0.1C to the activation voltage upper limit V max -V δ , and then discharge to the activation voltage lower limit V min + V δ , measuring different V δ The first coulombic efficiency of the formation under the conditions is the ratio of the formation capacity to the design capacity (480 mAh), where V max and V min The upper and lower voltage limits of the normal operation of the battery are measured for test example 1 respectively.
[0052] Cycle stability test: Place the formed batteries on a battery cycle test device with a discharge voltage range of their respective normal operating voltages. Perform a 5C charge and 5C discharge cycle test on the sodium ion battery at room temperature, and record the number of cycles at which the capacity tends to stabilize.
[0053] The first coulombic efficiency and cycle stability results are shown in Table 2.
[0054] Table 2
[0055]
[0056] According to electrochemical theory, the activation capacity of the battery increases with V δ However, as shown in Table 2, for the negative electrode titanium-based phosphate K 0.2 Na 0.8 The battery with TiOPO4 and KFSI added to the electrolyte has a high charge and discharge rate. δ When the activation capacity of the battery increases in the range of 0.2-0.6, the change is very small. This is because at the end of charging, the Na ions are first deintercalated, and then the K-Na ions are exchanged, and the voltage V for Na ion deintercalation is 脱嵌 Less than the voltage V required for K-Na ion replacement 交换 , that is, V 脱嵌 <V交换 , so appropriately reducing the voltage will not affect the battery capacity. δ Between 0.4-0.6, the activation voltage range is just V 脱嵌 and V 交换 In this voltage range, due to the presence of electrolyte additives, a protective film containing K is formed at the negative electrode to prevent the escape of K ions, further limiting the exchange of Na-K. Even when switching to normal charge and discharge, due to the presence of the protective film, there is no Na-K exchange between Na ions in the electrolyte and K ions at the negative electrode. The number of cycles of cycle stability is only the change of voltage adjustment, which is basically within 10 cycles, especially V δ When V is 0.4, the number of stable cycles is only 5. δ When it is less than 0.4, the activation voltage range is larger than the voltage range of Na-K exchange V 交换 , the electrolyte additive attached to the negative electrode surface first participates in Na-K exchange, rather than forming a protective film containing K ions. When switching to normal charge and discharge, Na-K exchange still occurs; when V δ When it is greater than 0.6, the activation voltage range is smaller than the voltage range of sodium ion deintercalation V 脱嵌 At this time, the battery's charge and discharge capacity suffers a certain loss, and the battery's initial efficiency is reduced to less than 90%. Therefore, when switching to normal charge and discharge, Na-K exchange will still occur, and the number of stable cycles is the longest.
[0057] For the negative electrode titanium-based phosphate KNa 0.8 TiO(PO4) 0.2 (P2O7) 0.8 The battery test results are similar to those of the negative electrode titanium-based phosphate K 0.2 Na 0.8 The TiOPO4 battery is similar.
[0058] However, for the battery with negative electrode titanium-based phosphate KNaTiOPO4, 0.2 Na 0.8 Compared with TiOPO4 batteries, due to the use of non-sodium-rich negative electrode materials, even with a specific voltage activation method, its coulomb efficiency is less than 90%, and the number of stable cycles has reached more than 100 times. This is mainly because the sodium-rich titanium-based phosphate K 0.2 Na 0.8 The sodium-rich state in the TiOPO4 lattice can form a strong coupling with the K ions in the site, reducing the escape of K ions.
[0059] For the negative electrode titanium-based phosphate K 0.2 Na 0.8 TiOPO4 and the electrolyte without additives, when there is no electrolyte additive, even if Vδ Between 0.4 and 0.6, since no protective film is formed on the negative electrode surface during formation, when switching to normal charge and discharge voltage, the Na-K exchange cannot be prevented, and the Na-K exchange continues, with the number of stable cycles lasting more than two hundred cycles.
[0060] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A sodium ion battery formation method, characterized in that: The steps include: S1. The sodium ion battery to be formed is allowed to stand for 15-60 minutes at a temperature of 60-92°C and a pressure of 0.2MPa-0.3MPa; The negative electrode of the sodium ion battery to be formed comprises a sodium-rich potassium titanyl phosphate carbon composite material, wherein the molecular formula of the sodium-rich potassium titanyl phosphate is K 1-x Na x+y TiO (PO4) 1-y M y , where x=0-0.8, y=0-0.8, x+y=0.5-0.8, M is a tetravalent anion SiO4 4- or P2O7 4- ; The electrolyte of the sodium ion battery to be formed includes a potassium ion additive; S2, at a temperature of 40-60°C and a pressure of 0.3MPa-0.5MPa, charge at a rate of 0.02-0.2C to the activation voltage upper limit Vact max , and then discharge to the activation voltage lower limit Vact min ; Among them, Vact max =V max -V δ , Vact min =V min + V δ , V δ =0.4-0.6v, V max and V min They are respectively the upper and lower voltage limits for normal battery operation.
2. The sodium ion battery formation method according to claim 1, characterized in that: The potassium ion additive is selected from potassium bis(fluorosulfonyl)imide and / or potassium bis(trifluorosulfonyl)imide.
3. The sodium ion battery formation method according to claim 2, characterized in that: The amount of the potassium ion additive added is 0.1%-1% of the mass of the electrolyte.
4. The sodium ion battery formation method according to claim 1, characterized in that: The mass ratio of sodium-rich potassium titanyl phosphate to carbon in the sodium-rich potassium titanyl phosphate carbon composite material is (0.7-0.99): (0.01-0.3).
5. The sodium ion battery formation method according to claim 1, characterized in that: The first coulombic efficiency of the sodium ion battery to be formed is greater than 90%.
6. The sodium ion battery formation method according to claim 1, characterized in that: The sodium ion battery to be formed also includes a positive electrode, which includes sodium iron pyrophosphate, with a molecular formula of Na 4-a Fe 3-b (PO4)2 (P2O7), where a=0-1, b=0-1.
7. The sodium ion battery formation method according to claim 1, characterized in that: The electrolyte solution further includes an electrolyte salt, and the electrolyte salt is selected from one or more of sodium hexafluorophosphate, sodium perchlorate, sodium bis(oxalate)borate, sodium bis(salicylate)borate and sodium tetraphenylborate.
8. The sodium ion battery formation method according to claim 1, characterized in that: The electrolyte further comprises an organic solvent, and the organic solvent is selected from one or more of ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate and diethylene glycol dimethanol ether.
9. A sodium ion battery prepared by the formation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Potassium titanyl phosphate film negative electrode material as well as preparation method and application thereof
CN111029573A
Sodium ion battery and formation method thereof
CN118712534A